Effects of Multiple Treatments of Formic Acid on the Chemical Properties and Structural Features of Bamboo Powder - Hui Qiao; Yue Liu; Yongshun Feng; Xin Pan; Xiaowei Zhuang; Jia Ouyang (Molecules)
Under mild conditions, formic acid effectively separates the components of lignocellulose, removing the majority of the hemicellulose and lignin from the cellulose. However, it has not yet been determined if multiple treatments with fresh formic acid may totally remove hemicellulose and lignin. In this study, fresh formic acid was used to repeatedly pretreat the bamboo powder, and the effect of multiple treatments on the physicochemical structure of the bamboo powder was investigated using changes in fractions, enzymatic hydrolysis, hydrophilicity, cellulose crystallinity, and lignin structure. Although the hydrophilicity of the powder rose as the number of treatments increased and the number of β-O-4 links in the lignin decreased, it was found that the bamboo powder still contained 5.4% lignin and 2.5% hemicellulose. The 48 h enzymatic yield increased with the number of treatments, with a 59.3% yield obtained at the fifth cycle. This study can serve as a foundation for further research into the mechanism of the influence of organic solvent pretreatment on lignocellulose structural integrity.